SMALLER FORAMINIFERS OF THE UPPER CARBONIFEROUS AUERNIG GROUP, CARNIC ALPS (AUSTRIA/ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
The micropaleontological components, particularly smaller foraminifers, from limestonesof theUpper Carboniferous Auernig Group (Carnic Alps, Austria/Italy) are described. Most of the taxa have been previously recorded from North America, Arctica and Russia (Urals, Donbass). The biostratigraphical value of Pseudovidalina, Nodosinelloides, Tezaquina and Vervilleina for the Oembourgian stage is recognized. The systematical part is principally devoted to generic discussion concerning Hemidiscus and Eolasiodiscus; Palaeobigenerina, Deckerella, Cribrogenerina and Climacammina; Ammovertella, Calcivertella and Calcitornella; Spireitlina and Pseudopaleospiroplectammina; Pseudovidalina and Raphconilia: Vervilleina and Tezaquina; and Nodosinelloides, Protonodosaria and Nodosaria.